ANALYSIS OF THE FACTORS CAUSING OF JUVENILE DELINQUENCY AND IMPLICATIONS ON COUNSELING SERVICES - Lasambouw, Senia Pradirga; Nurussakinah, Nurussakinah Daulay (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
This study aims to find out about the Analysis of the Causal Factors of Delinquency and Their Implications for Counseling Guidance Services for Mts Al-jam'iyatul Wasliyah Teimbung. The research method used is descriptive qualitative, namely a description of what happened in the field. The research subjects were counseling teachers, homeroom teachers, and several students of Mts Al-jam'iyatul Wasliyah Teimbung, through survey techniques. The instruments used in this study were documentation, interviews, and observations. Interviews were conducted with counseling teachers and homeroom teachers and observations were made by observing the condition of the school environment and the existence of the school. Data analysis techniques are carried out by collecting data, grouping data, analyzing data, and interpreting data which will be concluded as research results. The conclusion of this study is that the Analysis of the Causal Factors of Juvenile Delinquency and Their Implications for Guidance Counseling Services at Mts Al-jam'iyatul Wasliyah Tembung is in a fairly good category.